The place of filtration surgery in the treatment of adult onsets of primary glaucomas - Niżankowska, Maria Hanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The author presents contemporary opinion on the place of filtration surgery in the treatment of adult onsets of primary glaucoma. Increasing age and greater IOP fluctuation increase the odds of VF progression after surgical intervention. Retinal ganglion cell function, optic disc morphology as well as VF parameters, can be at least partially restored after surgical IOP reduction in early glaucoma. It is the most important, to choose the critical time for surgical intervention in the aim to achieve reversal of field loss.